Penggunaan Media Gambar Karikatur untuk Meningkatkan Minat dan Hasil Belajar Siswa - Sari, Lisi Guspita; Yuliasty, Penty; Rahyu, Venny Andeska; Petri, Lela Yauma; Prengki, Jek; Adisel, Adisel (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The aim of this study; 1) To find out the increase in student achievement; 2) To find out the activities of teachers and students in learning; 3) To determine the skills of teachers in managing learning; and 4) To find out student responses to learning in the use of picture media to get good learning outcomes in the Integrated Social Sciences class IX SMPN 3 Bengkulu City. The subjects of this study were students of class IX-2 SMP Negeri 3 Bengkulu City which consisted of 28 students. Data was collected using tests (pre-test and post-test) for student learning outcomes, using observation sheets for teacher and student activities, observation sheets for teacher skills in managing learning, and student response questionnaires on the use of picture media. Data analysis used descriptive statistics of percentages. The research results obtained; 1) The percentage of completeness individually increased, in cycle I there were 18 students who completed individually and 10 students who did not complete from 28 students (64%), in cycle II there were 24 students who completed individually and 4 students who did not complete from 28 students (86%). The percentage of classical completeness increased from 60% in the first cycle to 90% in the second cycle; (2) the activities of teachers and students increase to match the ideal percentage of time; (3) The skills of teachers in the application of the use of picture media increased from moderate (2.5) to good (3.7); and (4) students' responses to the use of picture media were 92.9% of the 28 students answered that they could clarify the understanding of the material being studied using picture media. In conclusion, the use of caricature media as a learning medium can increase the interest and learning outcomes of class IX-2 SMP Negeri 3 Bengkulu City students in Integrated Social Studies learning on population dynamics material. Keywords: Learning Outcomes, Social Studies, Caricature Image Media, Interest in Learning